Human Immunodeficiency Virus Type 1 Strains R5 and X4 Induce Different Pathogenic Effects in hu-PBL-SCID Mice, Depending on the State of Activation/Differentiation of Human Target Cells at the Time of Primary Infection - Fais, Stefano (American Society for Microbiology, 1999)
In a previous study, we had found that the extent of T-cell dysfunctions induced by a T-tropic strain of human immunodeficiency virus type 1 (HIV-1) in SCID mice reconstituted with human peripheral blood lymphocytes (hu-PBLs) (hu-PBL-SCID mice) was related to the in vivo state of activation of the human lymphocytes. In this article, we compared the effect of infection of hu-PBL-SCID mice with either T-tropic (X4) or M-tropic (R5) strains of HIV-1 by performing virus inoculation at either 2 h or 2 weeks after the hu-PBL transfer, when the human T cells exhibited a marked activation state or a predominant memory phenotype, respectively. A comparable level of infection was found when hu-PBL-SCID mice were challenged with either the SF162 R5 or the IIIB X4 strain of HIV at 2 h postreconstitution, while at 2 weeks, the R5 virus infection resulted in a higher level of HIV replication than the X4 virus. The R5 strain induced a marked human CD4(+) T-cell depletion along with a drop in levels of human immunoglobulin M in serum and release of soluble factors at both infection times, while the X4 virus induced severe immune dysfunctions only at 2 h. Of interest, injection of hu-PBLs into SCID mice resulted in a marked up-regulation of CCR5 on human CD4(+) T cells. The percentage of CXCR4(+) cells did not change after transplantation, even though a significant decrease in antigen expression was observed. Comparative experiments with two molecular clones of HIV-1 (X4 SF2 and R5 SF162) and two envelope recombinant viruses generated from these viruses showed that R5 viruses (SF162 and the chimeric env-SF162-SF2) caused an extensive depletion of human CD4(+) T cells in SCID mice at both 2 h and 2 weeks after reconstitution, while the X4 viruses (SF2 and the chimeric env-SF2-SF162) induced CD4 T-cell depletion only when infection was performed at the 2-h reconstitution time. These results emphasize the importance of the state of activation/differentiation of human CD4(+) T cells and gp120-coreceptor interactions at the time of primary infection in determining HIV-1 pathogenicity in the hu-PBL-SCID mouse model.